The impact of COVID-19 pandemic on hospital admissions for nine diseases in Iran: insight from an interrupted time series analysis - Sina Ahmadi; Ali Kazemi-Karyani; Nasim Badiee; Sarah Byford; Ali Mohammadi; Bakhtiar Piroozi; Satar Rezaei (Cost Effectiveness and Resource Allocation, 2022)
Abstract Background Associations between the COVID-19 pandemic and hospitalizations have not been studied Iran. This study aimed to examine the impact of the COVID-19 pandemic on hospital admissions for nine categories of disease in seven public hospitals in Kermsnahah city, the capital of Kermsnahah province, in the west of Iran. Methods Data on monthly hospitalization rates (number of hospitalizations per 100,000 population) were collected for nine categories of disease for a period of 40 months (23 months before and 17 months after the COVID-19 outbreak in Iran) from the health information systems of all seven public hospitals in Kermanshah city. Categories of disease included those related to pregnancy, childbirth and the puerperium period, neoplasms, diseases of the digestive, respiratory, circulatory, genitourinary and nervous systems, mental and behavioural disorders, and infectious and parasitic diseases. Population data were extracted from the Statistics Centre of Iran. An interrupted time series analysis with segmented regression was used to examine the impact of COVID-19 on hospital admissions. Findings Average monthly hospitalization rates fell for all nine categories of disease included in the study after the onset of the pandemic, with overall rates of 85.5 per 100,000 population in the period before the COVID-19 outbreak and 50.4 per 100,000 population after the outbreak began. The relative reduction in hospitalizations for the nine diseases was 56.4%. Regression analysis of monthly data indicated a sharp decrease in hospitalisations during the first month after the COVID-19 outbreak, which was statistically significant for all diseases (p < 0.001). After the initial reduction following onset of the pandemic, significant increases were observed for some diseases, including neoplasms (increase of 3.17 per 100,000 population; p < 0.001), diseases of the digestive system (increase of 1.17 per 100,000 population; p < 0.001) and diseases related to pregnancy, childbirth and the puerperium period (increase of 1.73 per 100,000 population). For other categories of disease, rates significantly declined, including infectious and parasitic diseases (decrease of 2.46 per 100,000 population; p < 0.001). Hospitalization rates did not increase to pre-pandemic levels for any disease, with the exception of those related to pregnancy, childbirth and the puerperium period. Conclusions Our study indicated that the COVID-19 pandemic had a significantly negative effect on hospitalizations in Iran. Although use of hospital care has gradually increased post-outbreak, it has yet to return to normal levels.